Lost to the collective : suicide and the promise of Soviet socialism, 1921-1929 - Pinnow, Kenneth Martin (Cornell University Press, 2010)
Arguing that the Soviet regime represented a particular response to the pressures & challenges of modernity, this book examines Soviet socialism, from its intense concern with the individual to its quest to build an integrated society, as one response to the larger question of human unity.